OPTIMALISASI KEMITRAAN MELALUI PERAN KADER SEBAGAI AGENT OF CHANGE PENINGKATAN CAPAIAN TIDAK MEROKOK DI RUMAH TANGGA - Ratna Dian Kurniawati; Imam Abidin; Nyimas Sopi Sibtiah (Universitas Mataram, 2022)
The Indonesian Ministry of Health always strives to improve the health status of the community, one of which is through the Clean and Healthy Life Behavior Program (PHBS). Increasing the success of PHBS in Riskesdas 2008, 2013 and 2018 through household PHBS indicators. Riskesdas 2018 shows 39.1% of households in Indonesia have PHBS. There are 5 indicators that are still below 80%, not smoking in the house is one of them. The implementation of PHBS requires the attention, support and participation of all levels of society.This community service aims to increase motivation and encourage the participation of cadres as agents of change to increase the number of not smoking in the house in the work area of ​​the Panyileukan Health Center UPT, Bandung City.The method used is counseling and socialization about the role of cadres as agents of change in an effort to increase the number of not smoking in the house then followed by the practice of self-hypnosis to control the urge to smoke.This community service activity was initiated by the Panyileukan Public Health Center UPT in collaboration with Bhakti Kencana University. Community Service was attended by 21 cadres in the working area of ​​the Panyileukan Health Center UPT. The activity begins with counseling about the dangers of smoking in the home and the importance of the role of cadres as agents of behavior change to stop smoking in the household. Followed by a self-hypnosis demonstration to control the urge to smoke which was learned by the cadre's mother. The activity went smoothly, the enthusiasm of the cadre mothers was expressed in a discussion session regarding the obstacles that are challenges and opportunities to address the problem of smoking in the house. The cadres are motivated to carry out their role as agents of change in the community who are responsible and play a role in improving the health status of the community.